PENINGKATAN KOMPETENSI GURU DALAM MENYUSUN SILABUS DAN RPP MELALUI SUPERVISI AKADEMIK DI SMP NEGERI 3 SUNGAI LALAK - Sujarno Sujarno (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2019)
The learning implementation plan is a guide to the steps that will be taken by the teacher in the learning process which is arranged in the activity scenario. But the fact is there are still teachers who do not compile a set of lessons such as syllabus and plan for implementing learning. The research was conducted at SMP Negeri 3 Sungai Lalak. This study uses school action research which consists of two cycles. The results of the study prove, the basic data of the teacher who compiled the learning device is 67% or as many as 8 teachers who collect. While the quality of the learning device is only 3 teachers with a large number of assessments of 70 with a percentage of 25% with very little category. In the first cycle the quantity of collection of learning devices increased to 92% while the quantity for the syllabus and lesson plans was above 70 with a percentage of 75% in the good category. In the second cycle, the quantity of teachers who compiled the syllabus increased to 100%. While the quality of the 12 teachers who compiled the syllabus and lesson plans, the assessment has been above 70 with a percentage of 100% in the excellent category. It can be concluded that by applying the academic supervision can improve the competence of teachers in preparing the syllabus and RPP at SMP Negeri 3 Sungai Lalak.